Analisis Strategi Marketing Mix Terhadap Peningkatan Jumlah Pengunjung Pada Kedai Kopi Ibrato Coffee Kabupaten Bandung - Iskandar, Ridwan; Wibowo, Sukarno; Purnama, Rusna (Jurnal Akademi Pariwisata Medan, 2025)
Marketing is an effort to maintain and keep a business growing and can help expand the business. This study aims to determine how to apply the 7P marketing mix to increase the number of visitors to the Coffee Shop called Ibrato Coffee, and to determine what factors are obstacles and supporters in its implementation. This study is a qualitative study with a description of the 7P variables in the marketing mix, namely product, price, place, promotion, people, process, physical evidence. This study uses interview data collection techniques, observation and documentation with purposive sampling techniques. The unit of analysis in this study consisted of 6 informants, consisting of the owner, employees and visitors of the Coffee Shop. The results of this study using interview analysis techniques, show that the marketing mix strategy applied at the Ibrato Coffee Shop to increase the number of visitors in the marketing process has been implemented well and effectively, and has good procedures in dealing with consumers. Consumers who visit are satisfied with the service provided